(3TQM cJGH GdCQHYI dHWdjehSs - (3CHh GdMSf Ydj Hf QVhGf Hf Ydj Hf LYaQ GdeJWHHs; (3HWdjehS GdMcje GdbdhPjs ((3CMeO Hf eMeO Hf CMeO Hf eMeO GdbQWHi GdjeGfi s)
(3ChdgG (B:s
(3bGd bUOfG Cf fTQM CbGhjd HWdjehS ai UfGYI GdbVGA HGdfLhe Ydi GdMhGOK s
(3BNQgG (B:s
(3aCeG Ef cGfJ GdfLhe ai GdWGdY hGdSYhO ai GdZGQH JeJ GdebGdI GdJGSYI ef JaSjQ hHJeGegG JeJ GdebGdI GdKGdKI dHWdjehS hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ai GdeYgO fSNI CNQi HYfhGfs
(3TQM GdebGdGJ GdCQHY dHWdjehS HQbe (B140 (3adcs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B638 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B886 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs